2011
DOI: 10.1002/chem.201002541
|View full text |Cite
|
Sign up to set email alerts
|

Regioselective Double Capping of Cyclodextrin Scaffolds

Abstract: Four different regioselective double capping reactions were applied either to α- or β-cyclodextrin (CD) scaffolds. The first, which relied on the use of a rigid, bulky dialkylating reagent containing two trityl-like subunits, gave access to an A,B,D,E-tetrafunctionalised β-CD regioisomer in large scale reactions. Two further capping reactions, involving the dianions PhP(2-) and S(2- , led to the synthesis of new C(1)-symmetrical β-cyclodextrins in which pairs of neighbouring glucose units are linked by very sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 36 publications
0
23
0
Order By: Relevance
“…[10] However, it is generally believed that high isoselectivity is incompatible with high enantioselectivity and vice versa. [11] We now describe the high performance of two crowded, chiral phosphanes, namely HUGPHOS-1 [12] and HUGPHOS-2, [13] in the asymmetric hydroformylation of styrene. Both ligands, which are respectively derived from a-and bcyclodextrin, have their phosphorus lone pair directed towards the appended cyclodextrin (CD) core.…”
mentioning
confidence: 99%
“…[10] However, it is generally believed that high isoselectivity is incompatible with high enantioselectivity and vice versa. [11] We now describe the high performance of two crowded, chiral phosphanes, namely HUGPHOS-1 [12] and HUGPHOS-2, [13] in the asymmetric hydroformylation of styrene. Both ligands, which are respectively derived from a-and bcyclodextrin, have their phosphorus lone pair directed towards the appended cyclodextrin (CD) core.…”
mentioning
confidence: 99%
“…We observed that by raising the temperature to 130 °C, the conversions remained practically unchanged (Table 3, entry 6). For comparison purposes, we also assessed the catalytic behaviour of the related diphosphine WIDEPHOS [39,52]. When using a WIDEPHOS:Pd ratio of 1:1, practically no reaction occurred (Table 3, entry 5).…”
Section: Resultsmentioning
confidence: 99%
“…In order to determine the enantiomeric excess, a sample of the reaction mixture (toluene) was treated with LiAlH 4 for 0.5 h. After filtration, the toluene solution containing enantiomeric alcohols was analysed by GC with a Chirasil-DEX CB column (25 m × 0.25 mm). HUGPHOS-1, HUGPHOS-2 [38], WIDEPHOS [39], and [PdCl(dmba)] 2 [89], were synthesized according to literature procedures. The synthesis and characterisation of compounds 5 , 9 , 12 and 13, as well as the general procedure for rhodium catalysed hydroformylation reactions have been reported in a preliminary communication [44].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We now describe the high performance of two crowded, chiral phosphanes, namely HUGPHOS‐112 and HUGPHOS‐2,13 in the asymmetric hydroformylation of styrene. Both ligands, which are respectively derived from α‐ and β‐cyclodextrin, have their phosphorus lone pair directed towards the appended cyclodextrin (CD) core.…”
Section: Methodsmentioning
confidence: 99%